DETERMINASI NIAT MENGGUNAKAN MOBILE INVESTMENT PADA GENERASI Z DI JABODETABEK - Ragasiwi, Diah Ayu; Sadat, Andi Muhammad; Monoarfa, Terrylina Arvinta (Yayasan Education and Social Center, 2025)
The digital transformation in the financial sector has significantly driven the growth of digital investment application usage in Indonesia. This study aims to analyze the influence of perceived usefulness, perceived ease of use, and perceived risk on users’ intention to use digital investment applications, with a case study of Bibit users in the Greater Jakarta area (Jabodetabek). A quantitative approach was employed by distributing questionnaires to 272 respondents, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that both perceived usefulness and perceived ease of use have a significant positive effect on intention to use, while perceived risk has a significant negative effect. These findings highlight the importance of developing user-friendly and beneficial features, as well as managing perceived risk, to encourage the intention to use digital investment applications, particularly among younger generations.